Computer networks : an open source approach - Lin, Ying-Dar; Baker, Fred , 1952-; Hwang, Ren-Hung (McGraw-Hill, 2012)
Intends to implement an open source approach, discussing the network layers, their applications, and the implementation issues. This book features 56 open-source code examples to narrow the gap between domain knowledge and skills